Comparison of PK/PD Targets and Cutoff Values for Danofloxacin Against Pasteurella multocida and Haemophilus parasuis in Piglets - Zhou, Yu-Feng; Sun, Zhen; Wang, Rui-Ling; Li, Jian-Guo; Niu, Chao-Yan; Li, Xian-An; Feng, Yun-Yun; Sun, Jian; Liu, Ya-Hong; Liao, Xiao-Ping (Frontiers in Veterinary Science, 2022)
Danofloxacin is a synthetic fluoroquinolone with broad-spectrum activity developed for use in veterinary medicine. The aim of this study was to evaluate the pharmacokinetic/pharmacodynamic (PK/PD) targets, PK/PD cutoff values and the optimum doses of danofloxacin against P. multocida and H. parasuis in piglets. Single dose serum pharmacokinetics was determined in piglets after intravenous and intramuscular administration of 2.5 mg/kg. Danofloxacin was well absorbed and fully bioavailable (95.2%) after intramuscular administration of 2.5 mg/kg. The epidemiological cutoff (ECOFF) values of danofloxacin from 931 P. multocida isolates and 263 H. parasuis isolates were 0.03 and 4 mg/L, respectively. Danofloxacin MICs determined in porcine serum were markedly lower than those measured in artificial broth, with a broth/serum ratio of 4.33 for H. parasuis. Compared to P. multocida, danofloxacin exhibited significantly longer post-antibiotic effects (3.18-6.60 h) and post-antibiotic sub-MIC effects (7.02-9.94 h) against H. parasuis. The mean area under the concentration-time curve/MIC (AUC24h/MIC) targets of danofloxacin in serum associated with the static and bactericidal effects were 32 and 49.8, respectively, for P. multocida, whereas they were 14.6 and 37.8, respectively, for H. parasuis. Danofloxacin AUC24h/MIC targets for the same endpoints for P. multocida were higher than those for H. parasuis. At the current dose of 2.5 mg/kg, the PK/PD cutoff (COPD) values of danofloxacin against P. multocida and H. parasuis were calculated to be 0.125 and 0.5 mg/L, respectively, based on Monte Carlo simulations. The predicted optimum doses of danofloxacin for a probability of target attainment (PTA) of >90% to cover the overall MIC population distributions of P. multocida and H. parasuis in this study were 2.38 and 13.36 mg/kg, respectively. These PK/PD-based results have potential relevance for the clinical dose optimization and evaluation of susceptibility breakpoints for danofloxacin in the treatment of swine respiratory tract infections involving these pathogens.